Implementasi Etika Berbahasa Indonesia dalam Komunikasi Bisnis di Perkantoran - Zahra, Gianita Aulia Zahra; Gita Pramesti; Grace Bryned Sawaki; Hafizh Bahrul Hayat; Lutfiah, Hanifah; Maryati, Hany; Rizkiyanfi, Mochamad Whilky (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to examine the implementation of ethical use of the Indonesian language in business communication within office environments. This research uses a qualitative approach with a descriptive method, examining various literature and relevant documents to understand how the use of polite, clear, rule-compliant, and empathetic language can strengthen the effectiveness of internal communication. Data were collected through a literature study and analyzed using content analysis techniques and triangulation to ensure the validity of the findings. The sources of data used include relevant documents and literature such as journals, scientific articles, and books. The results indicate that the implementation of ethical language use in Indonesian strengthens professional relationships, enhances organizational image, and fosters a harmonious work atmosphere. This study emphasizes the importance of mastering proper Indonesian in business as part of a strategy to build a professional and effective communication culture in the era of globalization